Table of Content - - (Journal of Islamic Sciences, 2025)
:Table of Content• The attitude of the People of the Book on Abrogation, and the Responses of Qur’anic Commentators: A comparative studyMs. Roaa Hameed Alyoubi, Prof. Sulaiman Qasim Al-Eid• Jurisprudence of verses from the book of Al-Hawi by Imam Al-Mawardi (deceased in 450 HA) Breastfeeding book (Collection and Study)Ms. Maryam Saad Al-Safari• The Ruling on Implementing Retribution Between Male and Female: A Comparative Jurisprudential Study under Omani LawMr. Ali Said Ali Ghafram Alshahri, Mr. Ahmed Mohammed Ali Ghafram Alshahri• The Recitation of Imam Abu Mujliz Al-Sudusi (d. circa 101 AH): A Compilation and Analytical StudyAsst. Prof. Muhammad Omar Majeed• Jizya in the modern stateMr. Ahmed Fathi Abdel-Azim• Semantic Potential in the Legal Meanings of Revealed Texts: An Analytical Reading of Its Inference Effects within Islamic ThoughtDr. Fazry Hamza
Keywords: Journal of Islamic Sciences